IEDR:an infrastructure enhanced DTN routing protocol - Zhen YU; Jing-dong XU; Jian-zhong ZHANG; Yu ZHANG (Tongxin xuebao)
To cope with un-ideal conditions in mobile network where connectivity is only intermittent,a novel DTN (delay tolerant network) routing protocol,IEDR,was proposed,which incorporates experiences gained before and strives to fully utilize node contacts for data exchange,in order to maximize delivery ratio and minimize delivery delay,while still with controlled overhead.Additionally,IEDR attempted to use wireless access points for data propagation,as access points were supposed to be widely deployed and interconnected with high speed,providing an opportunity to efficiently distribute data in large areas.The evaluation proves that IEDR is better than many classic DTN routing protocols.